(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
In the Hakusan area of Japan’s Ishikawa Prefecture, two villages, Fukaze and Higashi Futakuchi, roughly 350 years ago, developed and have continued to preserve bun’ya ningyō, puppetry combined with the bun’ya style of chanting, a precursor of bunraku. These traditions draw their tales from folk stories and the epic Heike Monogatari or Tale of the Heike. Although their puppets are basic in construction and use a simple form of manipulation, each of these related but distinct traditions captivates with its own unique figures, particular chanting style, and ingenious manipulation techniques. Equally worthy of attention are the roles these non-commercial traditions have played in uniting their rural communities and the deep attachment locals still have to their artform. With the erosion of rural lifestyles throughout Japan and the aging of the forms’ most engaged practitioners, it is difficult to anticipate the future of these arts. Along with Hakusan City Hall, the forms’ preservation associations have experimented with ways of documenting the traditions, finding new performance opportunities, and promoting their arts to a broader public.